Packet error rate analysis of decode-and-forward free-space optical cooperative networks in the presence of random link blockage. Issue 16 (8th September 2017) - Zdravković, Nemanja; Cvetkovic, Aleksandra; Milic, Dejan; Djordjevic, Goran T.
Abstract: This paper analyses end-to-end packet error rate (PER) of a free-space optical decode-and-forward cooperative network over a gamma–gamma atmospheric turbulence channel in the presence of temporary random link blockage. Closed-form analytical expressions for PER are derived for the cases with and without transmission links being prone to blockage. Two cooperation protocols (denoted as 'selfish' and 'pilot-adaptive') are presented and compared, where the latter accounts for the presence of blockage and adapts transmission power. The influence of scintillation, link distance, average transmitted signal power, network topology and probability of an uplink and/or internode link being blocked are discussed when the destination applies equal gain combining. The results show that link blockage caused by obstacles can degrade system performance, causing an unavoidable PER floor. The implementation of the pilot-adaptive protocol improves performance when compared to the selfish protocol, diminishing internode link blockage and lowering the PER floor, especially for larger networks.